Elastic liposomes as novel carriers: recent advances in drug delivery - Hussain A (Dove Medical Press, 2017)
Afzal Hussain,1,2 Sima Singh,1 Dinesh Sharma,3 Thomas J Webster,4 Kausar Shafaat,2 Abdul Faruk5 1Department of Pharmaceutical Sciences and Technology, Birla Institute of Technology, Mesra, Ranchi, Jharkhand, India; 2Faculty of Pharmacy, Sachchidananda Sinha College, Aurangabad, Bihar, India; 3Zifam Pyrex Myanmar Co. Ltd., Yangon, Myanmar; 4Department of Chemical Engineering, Northeastern University, Boston, MA, USA; 5Department of Pharmaceutical Sciences, Hemwati Nandan Bahuguna Garhwal University, Srinagar, Uttarakhand, India Abstract: Elastic liposomes (EL) are some of the most versatile deformable vesicular carriers that comprise physiologically biocompatible lipids and surfactants for the delivery of numerous challenging molecules and have marked advantages over other colloidal systems. They have been investigated for a wide range of applications in pharmaceutical technology through topical, transdermal, nasal, and oral routes for efficient and effective drug delivery. Increased drug encapsulation efficiency, enhanced drug permeation and penetration into or across the skin, and ultradeformability have led to widespread interest in ELs to modulate drug release, permeation, and drug action more efficiently than conventional drug-release vehicles. This review provides insights into the versatile role that ELs play in the delivery of numerous drugs and biomolecules by improving drug release, permeation, and penetration across the skin as well as stability. Furthermore, it provides future directions that should ensure the widespread use of ELs across all medical fields. Keywords: elastic liposomes, drug delivery, topical, transdermal, enhanced delivery